Fostering Students’ Listening Skills Through Youtube Videos Integrated with Edpuzzle Online Platform - Margawidjaya, Dwiseptiani; Herlina, Rina; Irianti, Leni (Journal of English Education Program (JEEP), 2024)
The aim of this study is to determine the goodness of using YouTube videos integrated with the EdPuzzle online platform on students' listening skills and students' perceptions on the use of the EdPuzzle online platform. The researcher applies a mixed-methods design, with the type of an embedded design. Regarding the quantitative paradigm, quasi-experimental one-group pre-test and post-test was employed. The subject of the research consisted of thirteen students sitting in the eleventh grade who were taken using a random sampling technique. The instruments to collect the data were tests and questionnaires. Data were collected by giving a pre-test followed by giving one treatment to thirteen vocational students after that the students were given a post-test and a questionnaire. The post-test which has a higher score than the pre-test proves the effectiveness of YouTube videos integrated with EdPuzzle as a medium to increase students’ listening skills. It is obvious that the use of YouTube videos integrated with EdPuzzle in teaching listening has a significant and effective impact on increasing students' listening skills. The result showed that the hypothesis is accepted in that there is the significant difference found in students' listening skills prior to and after being taught through YouTube videos that are integrated with the EdPuzzle online platform. In conclusion, the result of data analysis indicated quite clearly that the use of YouTube videos integrated with the EdPuzzle online platform is effective in increasing students' listening skills.